Graft preservation confers myocardial protection during coronary artery bypass grafting - Szalkiewicz, Philipp; Emmert, Maximilian Y.; Heinisch, Paul P.; Arnold, Zsuzsanna; Crailsheim, Ingo; Mach, Markus; Aschacher, Thomas; Grabenwöger, Martin; Winkler, Bernhard (Frontiers in Cardiovascular Medicine, 2022)
Background: During on-pump coronary artery bypass grafting (ONCAB), graft flushing for distal anastomoses testing also perfuses the downstream myocardium. This single center retrospective study evaluated the impact of specific preservation solutions on myocardial protection during ONCAB. Methods: Between 7/2019 – 3/2020 either DuraGraft (DG) or 0.9% Saline/Biseko (SB) was applied during 272 ONCAB. Overall, 166 patients were propensity matched into two groups. Cardiac enzymes [high-sensitive Troponin I (hs-TnI) and creatine kinase (CK)] were evaluated to seven days post-surgery. Results: Post-surgery, hs-TnI values were significantly lower from 3-6 hours (h) up to 4 days in the DG group: 3-6h: 4034 ng/L [IQR 1853-8654] vs 5532 ng/L [IQR 3633-8862], p=0.05; 12-24h: 2420 ng/L [IQR 1408-5782] vs 4166 [IQR 2052-8624], p<0.01; 2 days: 1095 ng/L [IQR 479-2311] vs 1564 ng/L [IQR 659-5057], p=0.02 and at 4 days: 488 ng/L [IQR 232-1061] vs 745 ng/L [IQR 319-1820], p=0.03. The maximum value: 4151 ng/L [IQR 2056-8621] vs 6349 ng/L [IQR 4061-12664], p<0.01 and the median area under the curve (AUC): 6146 ng/L/24h [IQR 3121-13248] vs 10735 ng/L/24h [IQR 4859-21484], p=0.02) were lower in the DG group. CK values were not significantly different between groups: maximum value 690 [IQR 417-947] vs 631 [464-979], p=0.61 and AUC 1986 [1226-2899] vs 2081 [1311-3063], p=0.37. Conclusions: Repeated graft flushing with DG resulted in lower Troponin values post-surgery suggesting enhanced myocardial protection compared to SB. Additional studies are warranted to further assess the myocardial protection properties of DG.